Can Third Party Funds, Financing to Deposit Ratio, and Capital Adequacy Influence Murabaha Financing? Study of Islamic Banks in Indonesia - Riska Nanda (Journal of Accounting Research, Organization and Economics, 2020)
Objective – This study aims to examine the effect of the factors that effect murabaha financing in Islamic Commercial Banks in Indonesia for the 2014-2018 period.  Design/methodology – The population in this study is 13 Islamic Commercial Banks in Indonesia which were established during 2014-2018, resulting in 62 observations. Data were examined using multiple linear regression analysis panel data.  Results – The results showed that third-party funds, optimizing the distribution of funding and capital adequacy have a joint effect on murabaha financing, third-party funds has a negative effect on murabaha financing, optimizing the distribution of financing that has a positive effect on murabaha financing, capital adequacy has a positive effect on murabaha financing.